FabToys: Large Arrays of Fabric-Based Pressure Sensors in Plush Toys to Detect Fine-Grained Interaction. - Kiaghadi, Ali; Huang, Jin; Homayounfar, Seyedeh; Andrew, Trisha; Ganesan, Deepak (Communications of the ACM, 2025)
The authors propose a product called "FabToy," a plush toy instrumented with a 24-sensor array of fabric-based pressure sensors. They explain that the toy will have dense spatial sensing coverage while also maintaining a natural fabric feeling and demonstrate that they can achieve high accuracy in detecting and localizing complex human interactions with the toy.